COLLATED UPSHOT OF INDIGENOUS DRUGS IN THE MANAGEMENT OF PARIKARTIKA W.S.R TO FISSURE-IN-ANO (AYUSHDHARA, 2016)
The deleterious dietetic habit and regimes leads to digestive disturbances; which further leads to disturbances in bowel habits. Among these disorders Parikartika is one in which patient experiences unendurable pain during and after defecation, burning sensation etc. due to agony of pain patient avoids to defecate, hence constipated. Fissure-in-ano afflicts both sexes but males suffer posteriorly while females suffer anteriorly. Until now some drugs were tried as an external application to relieve the pain and healing of the ulcer. This study was conducted to find the efficacy Ayurvedic drug over the standard modern drug. The patients attending OPD & IPD of Jammu Institute of Ayurveda and Research College and Hospital, were the source for study. 30 patients were clinically diagnosed as Parikartika were selected randomly and divided into two groups. Group A: Comprised of 15 patients and they were administered internally with Vedanasthapana Kshaya 1 Pala b.d, Erandbhrshta Haritaki at bed time, local application of Karpoora Ghrita 4 times a day and sitz bath with Panchvalakala Kwatha three times a day and before and after the defecation. Group B: Consisted of 15 patients and were administered internally with Ofloxacin, Ornidazole (200+500mg) combination b.d, Diclofenac sodium (50mg) b.d, Sodium picosulfate 1 tsf bedtime, sitz bath with lukewarm water. Duration of treatment was two months. The patients were followed up fortnightly for a period of two months. Both the groups had shown statistically significant changes. The therapy provided significant relief and healing of ulcer in this study. Therefore prescription from Bhaishjya Ratnawali of Karpoora Ghrita and Pachvalkala Kwatha along with Acharya Charak prescription of Vedanasthapana Kshaya and Anubhutta Yoga of Erandbhrshta Haritaki showed good and alternative result for the modern standard prescription.